2021
DOI: 10.1177/03000605211002379
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exosomal miR-596: a novel biomarker predicts survival in patients with idiopathic pulmonary artery hypertension

Abstract: Objective To determine if plasma exosomal microRNAs (miRNAs) can predict survival in patients with idiopathic pulmonary arterial hypertension (IPAH). Methods The study enrolled patients with IPAH that underwent right heart catheterization. Plasma was collected and exosomal miRNAs were extracted. Exosomes were evaluated using transmission electron microscopy, Western blot analysis and particle size distribution analysis. MiRNAs were evaluated using a miRNA microarray and validated using real-time polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Such studies are common and have identified valuable markers through the validation of clinical specimens. For example, low plasma levels of exosomal miR-150 (27) and miR-483 (250) and high levels of miR-596 (251) in patients with PAH suggested a poor prognosis; DQ593039 correlated significantly with diagnostic parameters in patients with CTEPH, and this piRNA showed potential value as a noninvasive screening agent (252). In practice, however, we do not know the donor cells, recipient cells, or specific mechanisms of abnormal exosomes in these disease groups, so further studies may be needed to elucidate the mechanisms of these markers in molecular, cellular, and animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are common and have identified valuable markers through the validation of clinical specimens. For example, low plasma levels of exosomal miR-150 (27) and miR-483 (250) and high levels of miR-596 (251) in patients with PAH suggested a poor prognosis; DQ593039 correlated significantly with diagnostic parameters in patients with CTEPH, and this piRNA showed potential value as a noninvasive screening agent (252). In practice, however, we do not know the donor cells, recipient cells, or specific mechanisms of abnormal exosomes in these disease groups, so further studies may be needed to elucidate the mechanisms of these markers in molecular, cellular, and animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, circulating miRNAs are a useful diagnostic and prognostic biomarker of PAH [ 49 , 50 ]. Previous studies have reported the association of circulating miRNAs, including miR-27b and miR-451 [ 51 ], miR-125a-5p [ 52 ], miR-509-3p [ 53 ], miR-206 [ 54 ], miR-483 [ 55 ], miR-211 [ 56 ], miR-143 [ 57 ], miR-596 [ 58 ], and miR-208-Mef2 [ 59 ] axis with the prognosis of PAH. The miR-29 family members have been reported as anti-fibrotic miRNAs [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…53 miR-596 derived from plasma exosomes can survive in patients with idiopathic pulmonary arterial hypertension, and it is a novel predictive biomarker. 54 High miR-596 levels in idiopathic pulmonary arterial hypertension have been detected, and they might be associated with severity and poor outcome from this condition. 54 The different expressions of exosomal miRNAs can affect pulmonary remodeling and pulmonary arterial pressure.…”
Section: Exosomal Mirnas In Idiopathic Pulmonary Artery Hypertensionmentioning
confidence: 99%